TO ON MINERALOGY OF MIAROLE CAVITIES IN GABBRO-ANORTOSITE OF KOROSTEN’ RLUTON - Kvasnutsya, I.; Zinchenko, O.; Mitrokhin, O. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
There is data of morphology and chemical composition of amphiboles from miarolitic cavities in gabro-anortozite of Korosten pluton. The extended-prismatic crystals of amphiboles enter in the complement of amphibole-quartz porous aggregate, discovered in a miarolitic cavity. Crystals are covered two-layer siliceous film, the overhead layer of which is made a globular silica, plates of plagioclase, needle-shaped and the short column crystals of fluorine-apatite, needle-shaped crystals of amphibole. The electron microprobe analysis shown that amphibole is ferro-aсtinolite and ferrous hornblende.